2017
DOI: 10.1128/jvi.00247-17
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptome Analyses Reveal that Potato Spindle Tuber Viroid Triggers Genome-Wide Changes in Alternative Splicing, Inducible trans -Acting Activity of Phased Secondary Small Interfering RNAs, and Immune Responses

Abstract: Many pathogens express noncoding RNAs (ncRNAs) during infection processes. In the most extreme case, pathogenic ncRNAs alone (such as viroids) can infect eukaryotic organisms, leading to diseases. While a few pathogenic ncRNAs have been implicated in regulating gene expression, the functions of most pathogenic ncRNAs in host-pathogen interactions remain unclear. Here, we employ potato spindle tuber viroid (PSTVd) infecting tomato as a system to dissect host interactions with pathogenic ncRNAs, using comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
121
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 83 publications
(105 reference statements)
14
121
1
1
Order By: Relevance
“…This remodeling effect of the virus on the host transcriptome is a common strategy exploited by the virus in hostvirus interactions and has been observed in various viruses [48][49][50]. Notably, a recent study showed that HSV-1 infection could not only result in changes in gene expression but also in alternative polyadenylation and splicing in the host transcriptome by influencing the host RNA processing [51]. However, several concerns about the alteration of RNA transcripts at the whole-transcriptome level, as a result of HSV-1 infection, especially the circular RNA transcriptome, have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This remodeling effect of the virus on the host transcriptome is a common strategy exploited by the virus in hostvirus interactions and has been observed in various viruses [48][49][50]. Notably, a recent study showed that HSV-1 infection could not only result in changes in gene expression but also in alternative polyadenylation and splicing in the host transcriptome by influencing the host RNA processing [51]. However, several concerns about the alteration of RNA transcripts at the whole-transcriptome level, as a result of HSV-1 infection, especially the circular RNA transcriptome, have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that trypsin significantly impacts on the free radical scavenging activities of flavonoids [8]. Our previous results also showed that trypsin scavenges superoxide anions (O 2 ‱ − ) and protects cells [9].In the area of phytopathology, transcriptomic analysis has been successful used on lots of plants [10][11][12][13]. However, few of transcriptomic works have been focused on the preservation of fruits.…”
mentioning
confidence: 86%
“…Exploiting the advantage in the present study, we explored the early molecular changes leading to the development of chlorosis using RNA-seq analysis. Although studies have shown the transcriptome changes in virus- and viroid-infected plants (Mochizuki et al ., 2014; Xia et al ., 2017; Zheng et al ., 2017), the strength of the present study is that we could detect any changes that precede detectable chlorosis.…”
Section: Discussionmentioning
confidence: 99%